Using Motivational General-Mastery Imagery to Improve the Self-efficacy of Youth Squash Players - O, Jenny; Munroe-Chandler, Krista J.; Hall, Craig R.; Hall, Nathan D. (Journal of applied sport psychology, 2014)
The current study examined whether an individualized motivational general-mastery MG-M imagery intervention consisting of daily imagery practice and weekly one-on-one guided imagery sessions could enhance self-efficacy in youth squash athletes (N = 5; M age = 10.80; SD = 1.93). A single-subject multiple-baseline design was employed spanning 13-18 weeks. Measures included the Sport Imagery Questionnaire for Children (Hall, Munroe-Chandler, Fishburne, & Hall et al., 2009) and a squash-specific self-efficacy questionnaire. Results indicated improvements in self-efficacy for 3 of the 5 athletes. The results from this study help inform researchers and practitioners regarding the use of MG-M imagery as a means to improve young athletes' self-efficacy.